Observing responses and informative stimuli - Wilton, R. N. (1971)
Pigeons were trained on a trial procedure. A trial began with the illumination of a pecking key by a white light. After a fixed interval, a key peck could turn the key to one of two equi-probable colors and produce a delayed trial outcome—an equi-probable occurrence of either reinforcement or nonreinforcement. After a trial, the key turned dark and the trial ended. The response could be made into an observing response by correlating the key colors with the outcomes. Response rates in the fixed interval then increased to a level greater than when the colors and outcomes were uncorrelated. In another phase, the response produced only the colors. The trial outcomes occurred some seconds after the fixed interval without a response being required. Correlating the colors with the outcomes again increased response rates. In a second experiment, a further condition was added in which reinforcement was the outcome on every trial. Response rates were lower than when there were equi-probable reinforcement and nonreinforcement outcomes with correlated colors, and about the same as when there were equi-probable outcomes with uncorrelated colors. The results suggest that stimuli providing information about the probability of reinforcement are themselves reinforcing.